2020
DOI: 10.1002/psp.2377
|View full text |Cite
|
Sign up to set email alerts
|

Rural residence and mortality in later life: Exploring the role of social integration and social support from a longitudinal perspective

Abstract: Though prior research has attempted to understand the impact of rural residence in early life on later mortality, the role of social integration and social support in explaining the residential mortality gap remains unclear. We first use the inverse probability treatment weighting method to address the potential selection bias in the data and then apply the complementary log–log modelling to a unique person‐wave data drawn from the Americans' Changing Lives study. The results indicate that (a) respondents livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
(107 reference statements)
0
3
3
Order By: Relevance
“…Likewise, the present research is partially consistent with prior population-level data indicating that there is a rural mortality penalty (Cossman et al, 2010;Cross et al, 2021;James, 2014;Singh & Siahpush, 2014) and further strengthens our ability to draw causal inferences about the impact of rurality on individuals' risk for mortality. Finally, it is worth noting that the present results stand in contrast to prior longitudinal work suggesting that there is a rural mortality advantage (Smith et al, 1995;Yang et al, 2021), which may be due to measurement differences. Residential location was self-reported in Yang et al (2021), whereas standard metropolitan statistical areas (SMSAs) were used in Smith et al (1995).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Likewise, the present research is partially consistent with prior population-level data indicating that there is a rural mortality penalty (Cossman et al, 2010;Cross et al, 2021;James, 2014;Singh & Siahpush, 2014) and further strengthens our ability to draw causal inferences about the impact of rurality on individuals' risk for mortality. Finally, it is worth noting that the present results stand in contrast to prior longitudinal work suggesting that there is a rural mortality advantage (Smith et al, 1995;Yang et al, 2021), which may be due to measurement differences. Residential location was self-reported in Yang et al (2021), whereas standard metropolitan statistical areas (SMSAs) were used in Smith et al (1995).…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, it is worth noting that the present results stand in contrast to prior longitudinal work suggesting that there is a rural mortality advantage (Smith et al, 1995;Yang et al, 2021), which may be due to measurement differences. Residential location was self-reported in Yang et al (2021), whereas standard metropolitan statistical areas (SMSAs) were used in Smith et al (1995).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies with county-level data, they found that the risk of death was highest among those living in central cities, whereas the risk of death was lowest for those living in rural areas, though the protective effects of rural areas weakened with increasing age. Additionally, Yang et al (2021) used longitudinal data from the Americans’ Changing Lives study (1986–2011) and showed that after accounting for age and sex, rural residents have a lower risk of death than those living in central cities. The discrepancy in findings regarding rural–urban differences in mortality risk across population-level and individual-level data is peculiar, especially considering that researchers do find longitudinal associations between rurality and individuals’ risk for various age-related diseases, such as Alzheimer’s disease (Glauber, 2022).…”
Section: Conceptualizing Place-based Disparities: Rurality–urbanicity...mentioning
confidence: 99%
“…PSS is also beneficial for the immune system in individuals with cancer, and those individuals with social support live approximately twice as long as those without such support [ 17 ]. A previous study has suggested that rural dwellers experience stronger social support than their urban counterparts [ 18 ].…”
Section: Introductionmentioning
confidence: 99%